Teaching adults - Rogers, Alan, 1933- (Open University Press, 2010)
This bestselling book will help anyone who is engaged in teaching adults. Whether you are working with groups or individuals, in a formal or informal setting, face-to-face or via distance learning channels, it will help you to develop a relationship with your student learners while increasing your understanding of yourself as a teacher.